Association of Femoroacetabular Impingement and Delayed Gadolinium‐Enhanced Magnetic Resonance Imaging of Cartilage: A Population‐Based Study. Issue 8 (4th July 2018) - Guo, Yimeng; Zhang, Honglin; Qian, Hong; Wilson, David R.; Wong, Hubert; Barber, Morgan; Forster, Bruce B.; Esdaile, John; Cibere, Jolanda; ,
Abstract : Objective: To assess the association of femoroacetabular impingement (FAI) and delayed gadolinium‐enhanced magnetic resonance imaging of cartilage (dGEMRIC) T1 relaxation values (RVs), and to evaluate whether subtypes of FAI (cam, pincer, and mixed) are associated with region‐specific dGEMRIC T1 RVs. Methods: A population‐based sample of white subjects with and without hip pain, ages 20–49 years, was selected through random‐digit dialing. A sample of 128 subjects underwent hip‐joint 3T dGEMRIC scans. Radiographic cam FAI was defined as an alpha angle >55°, while pincer FAI was defined by a lateral center edge angle >40°, or a positive cross‐over sign. Mixed impingement was defined by the presence of both cam and pincer impingement. Overall and region‐specific T1 RVs were compared between all FAI subtypes, using weighted linear regression analysis to account for sampling design of the study. Results: Subjects had a mean age of 38 years and 51% were female. We did not find an association of FAI with overall hip T1 RV (mean difference −15.5 [95% confidence interval −77.23, 47.14]). Significant associations of cartilage degeneration in anterior superior and central superior regions were found in subjects with mixed FAI compared to other FAI subtypes and non‐FAI subjects. Conclusion: Subjects with mixed FAI had reduced T1 RVs compared to other FAI subtypes. No substantial cartilage degeneration was found in pure cam or pincer FAI compared to no‐FAI hips. These results indicate that the presence of cam or pincer impingements alone does not suggest the beginning of cartilage degeneration. In contrast, the presence of both FAI subtypes is a risk factor for early cartilage damage.